Peran Ayah dalam Mendukung Perkembangan Sosial Anak Usia Dini di Desa Tamberu Laok Sokobanah Sampang - Amilia Febrian Mufarrohah; Raden Rachmy Diana (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to explore the role of fathers in supporting the social development of early childhood in Tamberu Laok Village, Sokobanah, Sampang. The background of this research is based on the observation that the role of fathers in parenting is often limited to economic aspects, while the caregiving role is predominantly assumed by mothers. This phenomenon can have a negative impact on children's social and emotional development, as the presence and involvement of fathers are crucial in shaping a child's character. This study employs a qualitative approach with a descriptive phenomenological method to depict the social reality in the field, using interviews with five heads of families in the village. The results of the study indicate that although fathers in Tamberu Laok Village are generally responsible for fulfilling the family's economic needs and maintaining harmonious relationships within the family, their involvement in child-rearing remains limited. This limitation affects children's social development, as evidenced by low self-esteem, difficulties in forming self-identity, and a lack of social skills. Additionally, the limited time spent with their fathers impacts the children's ability to manage their emotions. Therefore, this study emphasizes the importance of increasing fathers' involvement in caregiving to support the optimal social, emotional, and psychological development of children. In conclusion, the balance between the role of breadwinner and caregiver needs to be improved to create a harmonious family environment and well-rounded development for children in all aspects.